UPAYA MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM MENGGUNAKAN PEMBELAJARAN KOOPERATIF DI MTS AL-WASHILIYAH MEDAN JOHOR TAHUN 2019/2020 - Daulay, Budiman (Fakultas Agama Islam, 2020)
In an effort to increase the effectiveness of the learning process to achieve the best learning outcomes as expected, lesson planning is something that absolutely must be prepared by teachers every time they carry out the learning process. Although not necessarily everything that is planned will be implemented. Because it can be a class condition reflecting a request that is different from the plans that have been prepared, especially regarding strategies that are operational in nature. In the process of teaching and learning activities, cooperative methods are used to facilitate communication and can increase student interest in learning. The use of cooperative methods is very important in the ongoing teaching and learning process, because cooperative can create enthusiasm for student learning, and focus on learning. This research is conducted in an effort to improve student learning outcomes through the Cooperative Learning Method. VII MTS Al-Washiliyah Medan Johor Academic Year 2019/2020. Researchers use this type of classroom action research which consists of two cycles, each of which consists of planning, acting, observing, and reflecting. The subjects of the research were 47 grade students. The results obtained in research through the Cooperative Learning Method can be seen from the increase in the percentage of formative tests starting from pre-cycle I, and cycle II. In the pre-cycle 39% of students have completed, in cycle II. Referring to the results of this study, the researcher suggests that teachers further develop this method properly.